1985
DOI: 10.1093/nar/13.6.1965
|View full text |Cite
|
Sign up to set email alerts
|

Organization ofPlasmodium falciparum genome: 1. Evidence for a highly repeated DNA sequence

Abstract: Plasmodium falciparum DNA, isolated from the merozoite stage, was cleaved with HindIII and cloned in pBR322 and lambda L47.1 vectors. Plasmid clones containing 13.4, 7.0, 4.3, 4.1 and 1.5 kb inserts were characterized in some detail. The inserts contain several repeating units of smaller size. Nucleic acid hybridization studies showed that the repeat element is present in the Plasmodium DNA at a very high copy number and appears to be distributed widely throughout the genome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

1986
1986
1995
1995

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 25 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…A more rapid approach for detection has been based on the use of DNA probes. A repetitive DNA sequence {rep 20) from P. falciparum has been described by several independent investigators (Franzen et al 1984;Guntaka et al 1985;Bhasin et al 1985;Aslund et al 1985;Oquendo et al 1986). It consists of multiple, imperfect repeats of 21 base pairs and as many as 13 copies of the repeat can occur in tandem (Oquendo et al 1986).…”
Section: Introductionmentioning
confidence: 99%
“…A more rapid approach for detection has been based on the use of DNA probes. A repetitive DNA sequence {rep 20) from P. falciparum has been described by several independent investigators (Franzen et al 1984;Guntaka et al 1985;Bhasin et al 1985;Aslund et al 1985;Oquendo et al 1986). It consists of multiple, imperfect repeats of 21 base pairs and as many as 13 copies of the repeat can occur in tandem (Oquendo et al 1986).…”
Section: Introductionmentioning
confidence: 99%
“…In the subterminal chromosomal regions of most eukaryotic organisms studied to date, minisatellites have been found that consist of tandemly arranged repeat units of 21 bp to about 2 kb. For instance, subterminal minisatellites have been described in rye (Bedbrook et al 1980a), Plasmodium (,~s-lund et al 1985;Guntaka et al 1985;Oquendo et al 1986;Pace et al 1987), Dictyostelium (Emery and Weiner 1981), Saccharomyces , Drosophila (Bachmann et al 1990;Karpen and Spradling 1992;Levis et al 1993), Chironomus (Carmona et al 1985;Saiga and Edstr6m 1985), and man (Simmler et al 1987;Cheng et al 1989;Brown et al 1990;de Lange et al 1990;Rouyer et al 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Such repetitive DNA, however, is an excellent target for DNA-based diagnosis of infections caused by eucaryotic pathogens, because its abundance and rapid evolution allow sensitive and specific detection. Several plasmid clones have been isolated that may be suitable as oligonucleotide-based diagnostic probes for detection of Plasmodium falciparum (3,4,(7)(8)(9)16). Several of these clones have been sequenced and have been shown to contain a family of highly repetitive, somewhat degenerate 21-base-long DNA sequences (3,8,16).…”
mentioning
confidence: 99%